2020
DOI: 10.1108/jic-10-2019-0237
|View full text |Cite
|
Sign up to set email alerts
|

The present and future of intellectual capital in the healthcare sector

Abstract: PurposeThis systematic literature review analyzes and identifies research areas where researchers have already studied the role of intellectual capital (IC) in the healthcare sector. This review also analyzes how they carried out their work to understand future research directions.Design/methodology/approachThe analysis is conducted through a systematic literature review. Therefore, following systematic literature review protocol, it was possible to select 225 papers. An analysis of the content was done to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 94 publications
1
71
1
1
Order By: Relevance
“…This choice was made due to the high comprehensiveness and reliability in terms of metadata of these databases, as well as their diffuse use in other similar studies in the business and management fields (e.g. Ferenhof et al , 2015; Dada, 2018; Vrontis and Christofi, 2019; Paoloni et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This choice was made due to the high comprehensiveness and reliability in terms of metadata of these databases, as well as their diffuse use in other similar studies in the business and management fields (e.g. Ferenhof et al , 2015; Dada, 2018; Vrontis and Christofi, 2019; Paoloni et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown the importance of sense-making for hospital management with impacts on the health-care-welfare results, showing evidence of protocol reviews and better shared understanding about hazards and patient safety risks (Leykum et al , 2014; Hultin and Mähring, 2017). Paoloni et al (2020) emphasized the role of external knowledge from health networks and suppliers as part of the relational capital of health-care organizations. Penney et al (2018) described that a major problem in a US Veterans hospital was the high percentage of early readmissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Slightly better results were found in private hospitals, but the authors called for new studies in the field. A recent and systematic literature review about the role of intellectual capital in the health-care sector (Paoloni et al , 2020) concluded that the structural capital (focus on explicit knowledge) is widely discussed, whereas the relational capital (focus on external knowledge connections with universities, suppliers and health networks) has remained in the shadow, and human capital (focus on tacit knowledge) is the less studied component.…”
Section: Introductionmentioning
confidence: 99%
“…IC is composed of human capital, structural capital and relational capital. Human capital comprises the “skills, qualifications and experience” of the employees (Paoloni et al , 2020, p. 16). Structural capital is defined as the knowledge “embedded in organizational processes, systems, databases, patents and IPs” (Kianto et al , 2014, p. 364).…”
Section: Introductionmentioning
confidence: 99%
“…Although the KM and IC paradigms originally developed independently, interest in examining them jointly has been rising. Some authors interpret KM as the “dynamic” side of IC, effectively merging both concepts (Kianto, 2007; Paoloni et al , 2020). Other authors see IC and KM as conceptually distinct, yet complementary drivers of organizational performance (Seleim and Khalil, 2011; Hsu and Sabherwal, 2012).…”
Section: Introductionmentioning
confidence: 99%